Solvent-Selective Synthesis of Diaryl Disulfides and Arylthio Acetic Acids Using Thioglycolic Acid and Copper Catalysts - Kim, Kyungmi; Shin, Youngjin; Chae, Junghyun (Synlett, 2023)
An efficient Cu-catalytic protocol for the synthesis of diaryl disulfides from aryl iodides using thioglycolic acid as the sulfur source has been developed. This transformation was successful only in aqueous DMSO, and when the solvent system was switched to aqueous DMF, arylthio acetic acids, the immediate C–S coupling products, were obtained. Each synthetic protocol was optimized and applied to various aryl iodides to afford the corresponding products in good to excellent yields.
Keywords: diaryl disulfide; thioglycolic acid; arylthio acetic acid; copper catalyst; C–S coupling